A survey of antimicrobial use in dairy cows from farms in four regions of New Zealand. Issue 2 (4th March 2017) - Bryan, M; Hea, SY
Abstract: AIMS: To assess the use of antimicrobials in dairy cows over three seasons in a group of dairy farms within the Southland and South Otago region, and to assess antimicrobial use in one season in a group of monitored dairy farms in four regions of New Zealand. METHODS: Sales data were collated for all antimicrobials purchased by 399, 406 and 436 dairy farms in the Southland and South Otago regions for the 2012–13, 2013–14 and 2014–15 seasons, respectively, and from 108 dairy farms in the Manawatu, Taranaki, North Canterbury, and Southland and South Otago regions of New Zealand for 2014–15. Antimicrobials were categorised by class and product type (injectable, or dry cow or lactating cow intramammary). Antimicrobial usage was calculated as the mass of active ingredient (ai) per kg biomass, or population correction unit (PCU), with biomass estimated from the number of cows and heifers in the milking herd on 1 June multiplied by 458 kg. RESULTS: Estimated annual use of antimicrobials in the Southland and South Otago herds was 8.47, 9.58 and 9.54 mg ai/PCU for the three seasons, and for herds in the four regions was 8.65 mg ai/PCU for 2014–15. Penicillins were the most commonly used antimicrobials. Between 2012 and 2015, penicillin use increased from 5.75 to 7.44 mg ai/PCU, whereas there was a decrease in use of macrolides (1.19 to 1.04 mg ai/PCU) and cephalosporins (0.82 to 0.45 mg ai/PCU). Estimated annual use in 2014–15 by herds in Manawatu, Taranaki, North Canterbury, and Southland and South Otago was 8.93, 5.28, 6.44 and 9.97 mg ai/PCU, respectively, and also varied with size of herd. In these herds, injectable products were most commonly used (4.89 mg ai/PCU), followed by dry cow intramammary (3.04 mg ai/PCU), then lactating cow intramammary treatments (0.71 mg ai/PCU). CONCLUSIONS: The use of antimicrobials in dairy cows in New Zealand appears low by international standards, but varied across years and across regions. The vast majority of antimicrobials used by class were penicillins. This is the first attempt at a national assessment of antimicrobial use by volume and type for dairy cows in New Zealand and will aid in the progression of a strategy of reduction, refinement and replacement of antimicrobial use in animals.